Pengaruh Kinerja Mengajar Guru Terhadap Prestasi Belajar Matematika Peserta Didik di SMA Negeri 18 Makassar - Nurbaeti Nurbaeti; Asthi Nurawaliyah (Universitas Muslim Indonesia, 2022)
This research is ex post facto research. The purpose of this study was to determine: (1) whether there is influence of the pedagogic aspects of teacher performance on students' mathematics learning achievement at SMA Negeri 18 Makassar; (2) whether there is influence of the professional aspect of teacher performance on students' mathematics learning achievement at SMA Negeri 18 Makassar. The population in this study were 40 teachers at SMA Negeri 18 Makassar. The sample in this study were 6 math teachers at SMA Negeri 18 Makassar. Data collection techniques using questionnaires, report cards and documentation. Questionnaire method to collect teacher performance data, report cards to determine achievement in learning mathematics. The data analysis technique for the first hypothesis used normality analysis, while the third hypothesis test used multiple regression analysis at the significance level. The results showed that: (1) there was a significant effect of the pedagogic aspect of teacher performance on students' mathematics learning achievement at SMA Negeri 18 Makassar indicated by the value of t table > t count (1.317 > 0.811); (2) there is an influence of the professional aspect of teacher performance on students' mathematics learning achievement at SMA Negeri 18 Makassar indicated by the value of t table < t count (-0.259 > -0.811).